Chitosan nanoparticles on the improvement of thermal, barrier, and mechanical properties of high- and low-methyl pectin films - Lorevice, Marcos Vinicius (2016)
Non-biodegradable food packaging materials have caused serious environmental problems due to their inappropriate discard. Biodegradable and renewable polymers (e.g., polysaccharides), when reinforced with nanostructures, have been used to produce novel, eco-friendly food packaging as alternatives to replace conventional packaging. This study aimed at adding chitosan nanoparticles (CSNPs) to high-(HDM) and low-methyl (LDM) pectin matrices to produce HDM pectin/CSNP and LDM pectin/CSNP nanocomposite films, as well as at evaluating the effect of CSNPs on films' mechanical, thermal, and barrier properties. Also, CSNPs were characterized as to zeta potential, average diameter, and FT-IR, whereas nanocomposites' thickness, appearance, structure, morphology, mechanical, thermal, and barrier properties were analyzed. CSNPs presented average diameter and zeta potential near to 110 nm and 50 mV, respectively. The addition of CSNPs improved the mechanical properties, being tensile strength the most affected mechanical attribute (increased from 30.81 to 46.95 MPa and from 26.07 to 58.51 MPa for HDM pectin/CSNP and LDM pectin/CSNP, respectively). These results show that the produced pectin/CSNPs nanocomposites had improved mechanical properties when compared with control pectin films, making these novel materials promising for food packaging production. (C) 2015 Elsevier Ltd. All rights reserved.